Hydrodynamic impacts on tidal-scale dissolved inorganic nitrogen cycling and export across the estuarine turbidity maxima to coast - Yu, Dan; Chen, Nengwang; Cheng, Peng; Yu, Fengling; Hong, Huasheng (Biogeochemistry, 2020)
Estuarine turbidity maxima (ETM) is a transition zone subject to the influence of river flow and tides. Here we showed the distinct impacts of fluvial and tidal hydrodynamics on dissolved inorganic nitrogen (DIN) cycling and export across the ETM to coast. We conducted tidal-scale hourly measurements at the ETM zone of the Jiulong River Estuary in Southeast China in May and December 2015. Generally, ammonium-N (NH₄-N) and nitrate-N (NO₃-N) increased in ebb tides, primarily controlled by freshwater input. In contrast, nitrite-N (NO₂-N) increased in flood tides, largely due to the horizontal advection of NO₂-N rich water from the middle estuary (5–10 PSU). During the fresh–saline water mixing period with high suspended particulate matters (SPM), the stronger tides and smaller river discharge in December increased SPM and NO₂-N in the ETM, indicating stronger ammonium oxidation in the water column. During the low tide period when freshwater dominated and particles were deposited, the increase of NH₄-N in the water column was related to the external source supply (e. g., wetland effluent), while the decline of NO₃-N and NO₂-N was likely associated with denitrification occurring in anoxic fluid muds and sediments. The larger DIN flux was found in May with larger river discharge, weaker tides and longer duration of the freshwater dominated period than December. This study highlights the combined effects of river and tides on hydrodynamics, which largely determine the major N sources, processes (e.g., nitrification and denitrification) and DIN fluxes across the ETM to coast.